Evaluation of Cropland System Resilience to Climate Change at Municipal Scale Through Robustness, Adaptability, and Transformability: A Case Study of Hubei Province, China - Yan, Mingyan; Yang, Bohan; Sheng, Siyu; Fan, Xiangyu; Li, Xiaoyun; Lu, Xinhai (Frontiers in Ecology and Evolution, 2022)
Cropland system is one of the most sensitive socio-ecological systems to climate change such as drought and flood. Facing frequent extreme weather events worldwide, how to improve cropland system resilience to climate change (CSRCC) and thus ensure food production has been concerned. Although a small number of studies have tried to evaluate CSRCC through single or multiple indicators, few studies have considered from the perspective of the three basic capacities of resilience, i.e. robustness, adaptability, and transformability. Therefore, this study firstly constructs an evaluation index system from the three capacities of system resilience. Then, taking Hubei Province, China as a case, and comprehensively using the methods of Delphi, AHP, and TOPSIS to assess the spatio-temporal characteristics of CSRCC at municipal scale from 2011 to 2018. On this basis, the regional disparities of CSRCC between are analyzed by using Theil coefficient. The results show that CSRCC of Hubei Province fluctuates on a downward trend, with the lowest in 2012 and the highest in 2016. Most municipalities have witnessed a pattern of fluctuated decline, except for few ones in the plains. Generally, municipalities in the plains have greater scores, while some municipalities in the western and eastern hilly regions show higher adaptability and transformability. In addition, transformability rather than robustness and adaptability contributes more to the CSRCC at the municipal scale. At last, indicator selection against different research objects, influencing mechanism of CSRCC and policy implications are discussed. This study is expected to provide a reference for the practice in sustainable management and utilization of cropland system.